The influence of COVID-19 on the learning and developing processes of practical skills in military educational institutions - Bularca, Maria Cristina; Bumbuc, Stefania; Barsan, Ghita; Coman, Claudiu; Bucoi, Alexandru; Hertanu, Andreea; Netedu, Adrian; Aron, Ioan (Frontiers in Education, 2024)
During the COVID -19 pandemic, the educational process in military higher education institutions suffered underwent changes, especially in terms of carrying out practical activities. The purpose of the research was to analyze how the COVID -19 pandemic influenced the educational process and the leadership activities carried out in a Romanian military academy, in the context in which the practical activities had to be carried out in the online environment. Practical skills play an important role in the life of military students and they can help them within the process of becoming efficient leaders. In the context of the research, practical skills refer to decision-making abilities, conflict resolution skills, communication skills, the ability to delegate, or the capacity to motivate and inspire others. In order to conduct the re-search research, we used a quantitative approach. A questionnaire was applied to 288 students of "Nicolae Bălcescu" Land Forces Academy from Sibiu, Romania. The results of the research revealed that students pointed out the difficulty of interacting with their teachers, and of developing practical activities. While the opinions of the students were not influenced by their gender, they were influenced by the type of studies followed. Compared to bachelor students, master students were more affected by the changes which took place, and they believed to a higher extent that they possess leadership skills and that they have the necessary knowledge to lead a specific military group.